Implementation and Utilization of Smart Fisherman Application in Riau Islands Province - Darmawan, Eki (Department of Government Studies, Universitas Syiah Kuala, 2023)
The Smart Fisherman Application is an application designed to help fishermen obtain information about sea conditions, fish harvests and fish market prices. In the Riau Islands Province, this application is being introduced to improve the welfare of fishermen in the region. However, the use of this application is still faced with several obstacles and obstacles, such as limited internet access, low levels of digital literacy, and resistance from some fishermen in using the technology. However, the Nelayan Pintar application is considered to have great potential to increase fishermen's income and help in more sustainable management of marine resources. Therefore, research needs to be carried out to see the implementation and use of this application in the Riau Islands Province. This research uses qualitative research methods, using in-depth interview techniques and direct observation in the field.